2000
DOI: 10.1111/j.1651-2227.2000.tb00392.x
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of facial expressions of emotions in school‐age children: the intersection of perceptual and semantic categories

Abstract: Emotion cognition is a variegated domain which is differentially related to such areas of cognition as visuo-spatial and lexical semantic abilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
73
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(93 citation statements)
references
References 24 publications
16
73
1
Order By: Relevance
“…In that study, 8-year-olds showed larger congruency effects than adults for sad/fear stimuli in a speeded categorization task. Larger effects in children may be attributable to the slow development of adult-like sensitivity to sad and fear (Gao & Maurer, 2009;Kolb et al, 1992;Vicari et al, 2000), making their perception of these emotions in faces more susceptible to contextual influences.…”
Section: Discussionmentioning
confidence: 96%
“…In that study, 8-year-olds showed larger congruency effects than adults for sad/fear stimuli in a speeded categorization task. Larger effects in children may be attributable to the slow development of adult-like sensitivity to sad and fear (Gao & Maurer, 2009;Kolb et al, 1992;Vicari et al, 2000), making their perception of these emotions in faces more susceptible to contextual influences.…”
Section: Discussionmentioning
confidence: 96%
“…Even preschoolers discriminate happy faces from negatively valenced emotions (Widen & Russell, 2008a), and by 5 years of age children have adult-like sensitivity thresholds for facial displays of happiness (Gao & Maurer, 2009). In contrast, children continue to confuse fear with other negatively valenced emotions until at least 10 years of age (Camras & Allison, 1985;Durand et al, 2007;Gao & Maurer, 2009;Kolb et al, 1992;Vicari et al, 2000;Widen & Russell, 2003;Widen & Russell, 2008b). Given the ease with which children categorized happy and sad expressions, I hypothesized that, like adults, children's categorization of happy versus sad expressions would not be influenced by body posture.…”
Section: Methodsmentioning
confidence: 91%
“…This may in turn relate to more basic face processing difficulties amongst this group. Vicari et al (2000), for example, have noted that recognition of emotions such as fear and anger require the processing of both the upper and the lower parts of the face, while research by Carvajal, Ferández-Alcaraz, Rueda, & Sarrión (2012) has shown that adults with Down syndrome may focus on the lower more than the upper half of the face when processing emotional expressions. However, the extent to which such findings, in the absence of significant parallel difficulties with anger, can explain fear recognition difficulties in Down syndrome is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…These two components of emotion recognition -perceptual (facial expression recognition) and linguistic (emotion label understanding) -may be closely related, but follow very different developmental pathways (Vicari et al, 2000). While it is unlikely to be possible to disentangle them completely, a better understanding of how these two elements contribute towards any difficulties experienced by children with Down syndrome might begin to pave the way for the development of targeted interventions.…”
mentioning
confidence: 99%